The Effect of SGLT-2i and GLP-1RA on Major Cardiovascular Conditions: A Meta-Analysis - Jogimahanti, Arjun V.; Honan, Kevin A.; Ahmed, Talha; Leon-Novelo, Luis; Khair, Tarif (Cardiology and Cardiovascular Medicine, 2024)
Purpose: Sodium-glucose co-transporter 2 inhibitors (SGLT-2i) and Glucagon-like Peptide-1 Receptor Agonists (GLP-1RA) are two common anti-hyperglycemic agents prescribed by clinicians. The effects on cardiovascular conditions such as heart failure (HF) hospitalization, stroke, myocardial infarctions (MI), and other cardiovascular conditions are not well studied. The purpose of this study is to analyze existing data on the effect of SGLT-2i and GLP-1RA on preventing these cardiovascular conditions. Methods: A retrospective meta-analysis of all existing literature of the effect of SGLT-2i and GLP-1RA on the rates of the following categories was researched: primary cardiovascular outcomes, HF hospitalizations, atrial fibrillation (AF), stroke, MI and HF symptoms. Hazard ratios for each category were obtained, and overall Hazard Ratio (HR)’s to determine overall statistical significance were computed. Result: Both medication classes provided statistically significant reduction in preventing major cardiovascular events. Only SGLT-2i provided statistically significant reduction in heart failure hospitalizations. Only GLP-1RA provided statistically significant reduction in preventing stroke. Neither medication class provided a statistically significant benefit in preventing myocardial infarctions. More studies are needed on effects of either SGLT-2i or GLP-1RA agonists on preventing HF symptoms or AF. Conclusion: This study demonstrates that SGLT-2i and GLP-1RA are important for improving both diabetic and cardiovascular health. In patients at risk for a major cardiovascular event, SGLT-2i or GLP-1RA may be prescribed by clinicians. More studies must be performed to draw more conclusions.